Understanding the role of gender in fishing community development - Jimenez, Caridad N. (Iloilo City UP Visayas, 2003)
"The paper presents gender situations in fishing communities in Ivory Coast, Guinea, Tanzania, Myanmar, Lao PDR, India, Philippines, Peru and Japan as presented by the participants from these countries. Women's role include reproductive, social, economic, and productive responsibilities within and outside the family, including the harvesting, processing, transport and marketing of aquatic products. However, the women in fishing communities in most of these countries do not enjoy the same benefits and opportunities as the males, even if national legislation provides for equitable access to basic human and social rights. The lack of comprehensive gender data makes it difficult to address the problems faced by women in fishing communities. Studies have shown that for any development program to be truly meaningful and sustainable, the women sector should not be overlooked because they are significant stakeholders in the community."
Keywords: Sex role; Community development